2022
DOI: 10.1002/advs.202204522
|View full text |Cite
|
Sign up to set email alerts
|

LCK‐Mediated RIPK3 Activation Controls Double‐Positive Thymocyte Proliferation and Restrains Thymic Lymphoma by Regulating the PP2A‐ERK Axis

Abstract: Receptor‐interacting protein kinase 3 (RIPK3) is the primary regulator of necroptotic cell death. RIPK3 expression is often silenced in various cancer cells, which suggests that it may have tumor suppressor properties. However, the exact mechanism by which RIPK3 negatively regulates cancer development and progression remains unclear. This report indicates that RIPK3 acts as a potent regulator of the homeostatic proliferation of CD4+CD8+ double‐positive (DP) thymocytes. Abnormal proliferation of RIPK3‐deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Trp53 KO mice have been extensively used to study, not only the role of p53 as a tumor suppressor in vivo, 43–45 but also its interconnection with different proteins that participate in critical signaling pathways during carcinogenesis 46,47 . Our previous study in Trp53 KO mice demonstrated that Sphk1 deletion resulted in a senescence phenotype in the thymus, and as a consequence, Trp53 KO Sphk1 KO mice were protected against thymic lymphoma development 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Trp53 KO mice have been extensively used to study, not only the role of p53 as a tumor suppressor in vivo, 43–45 but also its interconnection with different proteins that participate in critical signaling pathways during carcinogenesis 46,47 . Our previous study in Trp53 KO mice demonstrated that Sphk1 deletion resulted in a senescence phenotype in the thymus, and as a consequence, Trp53 KO Sphk1 KO mice were protected against thymic lymphoma development 19 .…”
Section: Discussionmentioning
confidence: 99%